ANALISA PENGARUH ADMIXTURE TERHADAP ABU TERBANG (FLY ASH) DAN BOTTOM ASH - Redaksi Tim Jurnal (FORUM MEKANIKA, 2017)
With improve the quality of concrete is by using the addition of admixture. By adding admixture Silica fume and superplasticizer is expected to improve concrete quality in concrete using fly ash and bottom ash. The main objective of this research is to know the value of concrete compressive strength, slump test value, fresh concrete temperature and setting time in concrete using fly ash and bottom ash by 0%, 5%, 10%, 15%, 20% and 25% by weight of cement, with variations of silica fume 0%, 2%, 4%, 6 %, 8%, 10% of the weight of cement that has been reduced by the weight of fly ash and bottom ash and added with superplasticizer of 2% of the water requirement. The planned concrete quality was 41.7 MPa at 28 days, with the sample tested at age 7, 14, 28 days. Based on the results of the highest concrete compressive strength test for fly ash concrete (fly ash) is found in FA mixture variation 10%, SP 4%, SF 2% that is equal to 56,16 MPa. And for mixed bottom ash the highest compressive strength on mixed variation of BA 5%, SF 2%, SP 2% is equal to 49,82 MPa. Fresh concrete temperature variation of FA mixture 5%, SF 2%, SP 2% and BA 5%, SF 2%, SP 2% rose one degree from normal concrete temperature. Setting time generated on mixed concrete FA 5%, SF 2%, SP 2% has the fastest initial time setting ie 251 minutes of all variations of concrete mix.